Ultrasound evaluation of non-cystic renal masses and correlation with ultrasound guided fine needle aspiration cytology/biopsy - Chhadi, Shyam; Chhadi, Tulsi; Limbgaonkar, Jalinder (International Journal of Advances in Medicine, 2019)
Background: The purpose of present study was to identify sonologically, the cystic and non-cystic renal mass lesions, to attempt differentiating benign lesions from the malignant ones and to correlate ultrasound findings with ultra sonographically guided cytological or pathological findings. Methods: In this hospital based prospective observational study, all the patients with confirmed renal mass were subjected to USG guided fine needle aspiration cytology (FNAC). All the patients presenting with lump in abdomen, haematuria or pain in abdomen, wherein the clinical diagnosis of renal mass was being considered by the clinician, were enrolled for the study. Total 54 participants were enrolled. Those with confirmed renal mass were subjected to USG guided FNAC and which was carried out in supine position by transabdominal route in all patients. Results: About 42 participants were retained for final analysis; since FNAC was not possible in 12 patients. Pain in abdomen (36, 85.7%), mass in abdomen (34, 81%) were the most predominant clinical findings. Mixed echogenicity was the commonest echo pattern (42, 77.7%) on ultrasonography. Histopathologic/cytologic examination of the 39 malignant cases confirmed renal cell carcinoma (18, 46.5%) to be the commonest malignancy, followed by Wilms’ tumour (10, 26%). Out of the 39 cases in which clinico-radiological diagnoses were correlated with histo-cytological diagnoses, it was found to be consistent in 30 (77%) cases and inconsistent in 9 (23.1%) cases. Conclusions: Fine needle aspiration cytology/biopsy performed under ultrasonography guidance demonstrates high diagnostic accuracy. It is hence recommended as part of fundamental approach to the diagnosis of non-cystic renal mass.